Changes in basic composition and in vitro digestive characteristics of pork induced by frozen storage - Wang, Rui; Liu, Yongqing; He, Ying; Feng, Caiping; Xia, Xiufang (Frontiers in Nutrition, 2025)
IntroductionFrozen pork can reduce the quality of the meat and alter the digestibility and bioavailability of meat proteins in the human body. In this study, we investigated the changes in the basic composition during frozen storage and their effects on the structural properties of digestion products after protein digestion.MethodsThe impacts of frozen storage at different temperatures (−8, −18, −25, and −40°C) and for different times (1, 3, 6, 9, and 12 months) on the basic components and in vitro digestive characteristics of pork were evaluated.ResultsThe moisture, crude fat, and protein contents decreased with extended storage and increased temperature, whereas muscle juice loss increased (p < 0.05). During in vitro digestion of samples frozen at −8°C for 12 months, trichloroacetic acid (TCA)-soluble peptides were decreased by 25.46% and 14.37% in the gastric and small intestinal phases, respectively, compared with fresh samples. Confocal laser scanning microscope (CLSM) showed that samples stored at −8°C had the largest particle size after digestion. Disruption of protein structure was confirmed by the decrease in α-helix, β-turn, and fluorescence intensity (all p < 0.05) and the increase in β-sheet, random coil, and maximum fluorescence wavelength of the digestion products of samples frozen at −8°C (all p < 0.05).DiscussionTherefore, long-term high-temperature frozen storage brought about a significant decline in basic components of muscle and acceleration of loss of protein structural integrity after digestion.